Common wealth economics for a crowded planet - Sachs, Jeffrey (New York Penguin, 2008)
In Common Wealth, Jeffrey D. Sachs-one of the world's most respected economists and the author of The New York Times bestseller The End of Poverty- offers an urgent assessment of the environmental degradation, rapid population growth, and extreme poverty that threaten global peace and prosperity. Through crystalline examination of hard facts, Sachs predicts the cascade of crises that awaits this crowded planet-and presents a program of sustainable development and international cooperation that will correct this dangerous course. Few luminaries anywhere on the planet are as schooled in this daunting subject as Sachs, and this is the vital product of his experience and wisdom.
Includes bibliographical references (pages 349-369) and index.
Keywords: BUSINESS & ECONOMICS / Development / Sustainable Development; Economic policy; Sustainable development; Economic policy; Sustainable development; Electronic books